Case Report: Unmasking catatonia in adolescents: a potential triggering role of corticosteroids in two clinical cases - Margherita De Biase; Roberto Averna; Gianluca Sesso; Milena Labonia; Stefano Vicari (Frontiers in Psychiatry, 2026)
Background Catatonia is a transdiagnostic syndrome marked by motor, behavioral, and autonomic disturbances. Corticosteroids, commonly used to treat suspected neuroinflammatory conditions, may rarely precipitate or exacerbate psychiatric symptoms, including catatonia, in children and adolescents. Methods We describe two adolescent girls who developed catatonia following corticosteroid therapy for suspected encephalitis, despite negative cerebrospinal fluid and blood markers. Clinical courses, diagnostic workups, and therapeutic strategies (including benzodiazepines, antipsychotics, and immunomodulatory treatments) are detailed. A literature review of steroid-induced neuropsychiatric complications in pediatric populations was also performed. Results Both patients experienced temporal association between corticosteroid exposure and onset of catatonia. Standard first-line treatments were insufficient, and stabilization required antipsychotic therapy, including clozapine. Gradual improvement in baseline clinical status and recovery of lost functional abilities were observed during follow-up. These cases underscore that corticosteroid-induced catatonia, though rare compared to steroid-related psychosis, can occur in adolescents and may complicate the differential diagnosis of neuropsychiatric syndromes. Conclusions While corticosteroids remain essential for treating neuroinflammatory conditions, clinicians should be aware of the potential for severe psychiatric adverse effects, including catatonia, in pediatric patients. Careful differential diagnosis, interdisciplinary collaboration, and timely psychiatric intervention are critical to avoid iatrogenic worsening. Further research is needed to clarify underlying neurobiological mechanisms and identify markers of vulnerability, promoting safer and more personalized treatment approaches in children and adolescents.